Running for Exercise Mitigates Age-Related Deterioration of Walking Economy - Ortega, Justus D. (PLoS One, 2014)
INTRODUCTION: Impaired walking performance is a key predictor of morbidity among older adults. A distinctive characteristic of impaired walking performance among older adults is a greater metabolic cost (worse economy) compared to young adults. However, older adults who consistently run have been shown to retain a similar running economy as young runners. Unfortunately, those running studies did not measure the metabolic cost of walking. Thus, it is unclear if running exercise can prevent the deterioration of walking economy. PURPOSE: To determine if and how regular walking vs. running exercise affects the economy of locomotion in older adults. METHODS: 15 older adults (69±3 years) who walk ≥30 min, 3x/week for exercise, “walkers” and 15 older adults (69±5 years) who run ≥30 min, 3x/week, “runners” walked on a force-instrumented treadmill at three speeds (0.75, 1.25, and 1.75 m/s). We determined walking economy using expired gas analysis and walking mechanics via ground reaction forces during the last 2 minutes of each 5 minute trial. We compared walking economy between the two groups and to non-aerobically trained young and older adults from a prior study. RESULTS: Older runners had a 7–10% better walking economy than older walkers over the range of speeds tested (p = .016) and had walking economy similar to young sedentary adults over a similar range of speeds (p = .237). We found no substantial biomechanical differences between older walkers and runners. In contrast to older runners, older walkers had similar walking economy as older sedentary adults (p = .461) and ∼26% worse walking economy than young adults (p<.0001). CONCLUSION: Running mitigates the age-related deterioration of walking economy whereas walking for exercise appears to have minimal effect on the age-related deterioration in walking economy.